2013
DOI: 10.1016/j.bcp.2012.12.012
|View full text |Cite
|
Sign up to set email alerts
|

The vasorelaxant effects of 1-nitro-2-phenylethane involve stimulation of the soluble guanylate cyclase-cGMP pathway

Abstract: 1-Nitro-2-phenylethane is the first organic NO₂-containing molecule isolated from plants. It possesses interesting hypotensive, bradycardic, and vasodilator properties, but the mode by which it induces vasorelaxation is still unknown. The underlying mechanism involved in the vasodilator effect of 1-nitro-2-phenylethane was investigated in rat aorta. The vasorelaxant effects of 1-nitro-2-phenylethane did not depend on endothelial layer integrity, and the effects were refractory to L-N(G)-nitroarginine methyl es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…This pharmacological potency was lower than that evoked by other structurally related nitro compounds in the same preparations. The relaxant effects of its analogues on the contractions induced by phenylephrine yielded EC 50 varying between ~30 to 230 μ m . In common, these studies dealt with compounds possessing the NO 2 group in the α‐ or β‐carbon of the aliphatic chain ( Figure , panels c to f).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This pharmacological potency was lower than that evoked by other structurally related nitro compounds in the same preparations. The relaxant effects of its analogues on the contractions induced by phenylephrine yielded EC 50 varying between ~30 to 230 μ m . In common, these studies dealt with compounds possessing the NO 2 group in the α‐ or β‐carbon of the aliphatic chain ( Figure , panels c to f).…”
Section: Discussionmentioning
confidence: 99%
“…Substitutions in the aliphatic chain have been demonstrated to impact directly in their effects. 1‐Nitro‐2‐phenylethane ( Figure c), for instance, relaxes rat aorta preparations , but its analogue β‐phenylethylamine ( Figure a) causes aortic constriction in vitro, probably by acting on specific trace‐amine associated receptors . The nitro compound 2‐nitro‐1‐phenyl‐1‐propanol ( Figure d) relaxes rat aorta and mesenteric arteries , whereas its analogue phenylpropanolamine ( Figure b), a sympathomimetic active principle of over‐the‐counter nasal decongestants, reveals vasoconstrictor properties .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For an endothelium-independent vasodilator, possible mechanisms that may be involve in its inhibition of any of the downstream steps in the contractile apparatus (Allen and Walsh, 1994;Brito et al, 2013;Park et al, 2009).…”
Section: Serum Calcium Channel Blocking Effect Of Nbf-asmementioning
confidence: 99%
“…For example, resolving the crystal structure of the binding of the sGC activator BAY 60–2770 to an NO-sensitive heme domain homologous to sGC demonstrated that BAY 60–2770 shows a slightly more efficient conformational shift of the heme-binding domain than its parent compound cinaciguat, explaining its marginally more potent stimulation of sGC activity [48*]. And finally, the vasodilatory molecule 1-nitro-2-phenylethane was recently characterized as a novel heme-dependent sGC stimulator, distinct from the previously discovered riociguat-related compounds [49]. All these compounds hold great therapeutic potential in a variety of cardiovascular and other defects related to sGC dysfunction.…”
Section: Development and Characterization Of New Sgc Stimulating And mentioning
confidence: 99%